The relationship between inspiration as a psychological construct, temperament, and positive affect - Fulmer, Russell Dwight (Kansas State University, 2007)
The purpose of the current study was to identify if any significant relationships between inspiration, temperament, and positive affect existed. The dependent variable was inspiration, which was measured by the Inspiration Scale (IS). Temperament was measured by the Keirsey Temperament Sorter II and positive affect by the Positive and Negative Affect Schedule (PANAS). One hundred forty-five students attending a large Midwestern university and small community college participated. Initially, participants completed the Keirsey Temperament Sorter II online. The IS and PANAS were administered in the student’s classroom. The data were consequently analyzed to determine if there was a correlation between inspiration and temperament, inspiration and positive affect, and inspiration and the combined effects of temperament and positive affect. The results were mixed: 1. No relationship between inspiration and temperament was discovered. ANOVA results indicated that mean inspiration scores for each temperament did not vary significantly. 2. A relationship was identified between inspiration and positive affect. Regression results suggested a positive linear relationship between inspiration and positive affect scores. 3. When inspiration was correlated with positive affect and temperament combined, no relationship was discovered. A 2 x 4 ANOVA showed no correlation between the variables. The implications these results have on psychology and counseling are discussed, along recommendations for future research. Additionally, limitations of the study, such as inherent risks associated with using self-report measures, are mentioned. The study concludes with a discussion of how future research can investigate inspiration, temperament, and positive affect.
Keywords: Inspiration; Temperament; Positive affect; Education, Guidance and Counseling (0519)